1998
DOI: 10.1016/s0002-9440(10)65701-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Inhaled Urban Particles and Ozone

Abstract: We studied acute responses of rat lungs to inhalation of urban particulate matter and ozone. Exposure to particles (40 mg/m3 for 4 hours; mass median aerodynamic diameter, 4 to 5 microm; Ottawa urban dust, EHC-93), followed by 20 hours in clean air, did not result in acute lung injury. Nevertheless, inhalation of particles resulted in decreased production of nitric oxide (nitrite) and elevated secretion of macrophage inflammatory protein-2 from lung lavage cells. Inhalation of ozone (0.8 parts per million for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(42 citation statements)
references
References 35 publications
2
39
0
1
Order By: Relevance
“…The vasopressor response was directly associated with environmental fine particle concentrations. These findings suggest that the vasoconstriction observed in the brachial artery [50] occurs in the resistance microvasculature as well, perhaps due to enhanced endothelin expression [49] and sympathetic nervous system activity [38]. We therefore speculate that chronic exposure to fine particulate air pollution, at the levels encountered in present-day industrialized nations, may be a previously unappreciated risk factor for developing essential hypertension.…”
Section: Implications For Essential Hypertensionmentioning
confidence: 84%
See 1 more Smart Citation
“…The vasopressor response was directly associated with environmental fine particle concentrations. These findings suggest that the vasoconstriction observed in the brachial artery [50] occurs in the resistance microvasculature as well, perhaps due to enhanced endothelin expression [49] and sympathetic nervous system activity [38]. We therefore speculate that chronic exposure to fine particulate air pollution, at the levels encountered in present-day industrialized nations, may be a previously unappreciated risk factor for developing essential hypertension.…”
Section: Implications For Essential Hypertensionmentioning
confidence: 84%
“…Rats exposed to urban particulate matter were found to have increased circulating plasma levels of endothelin-1 [49], a marker for increased cardiovascular mortality. With these findings in mind, we investigated the effect of short-term PM 2.5 and ozone inhalation on vascular reactivity in healthy adults [50••].…”
Section: Vascular Functionmentioning
confidence: 99%
“…284 PM exposure has also been associated with increased blood pressure in cardiac rehabilitation patients 281 and in adults with lung disease, 279 increased vasoconstriction in the pulmonary vessels of rats, 400 increased circulating levels of the vasoactive peptide endothelin in rats, 401 and elevated levels of endothelin in animals for 2 hr to up to 2 days after urban PM pollution. 402 Brook et al 250 argue that arterial vasoconstriction is a likely explanation for the PM and exercise induced ischemia (as measured by ST-Segment depression in Pekkanen et al 275 ) and enhanced cardiac ischemia in dogs exposed to concentrated PM air pollution. 379 van Eeden et al 347 note that the time course of elevated endothelin observed in animals 402 is consistent with the time course observed in recent studies of PM exposure and MI events.…”
Section: Vasculature Alterationsmentioning
confidence: 99%
“…402 Brook et al 250 argue that arterial vasoconstriction is a likely explanation for the PM and exercise induced ischemia (as measured by ST-Segment depression in Pekkanen et al 275 ) and enhanced cardiac ischemia in dogs exposed to concentrated PM air pollution. 379 van Eeden et al 347 note that the time course of elevated endothelin observed in animals 402 is consistent with the time course observed in recent studies of PM exposure and MI events. 259,260 Because they are so closely linked to pulmonary and systemic inflammation, mechanisms related to vasculature alterations cannot be considered independent of previously discussed COPD and inflammation/atherosclerosis-related pathways.…”
Section: Vasculature Alterationsmentioning
confidence: 99%
“…The Ottawa dust (EHC-93) was a gift of Dr. R. Vincent (Environmental and Occupational Toxicology Division, Environmental Health Directorate, Health Canada, Ottawa, Ontario). In brief, EHC-93 contains profiles and amounts of polycyclic aromatic hydrocarbons, ions, and metals comparable to those of the standard reference materials 1648 (urban particulate matter) and 1649 (organics) of the National Institute of Standards and Technology (Gaithersburg, MD), and to a range of fine particulate materials recovered by field sampling (Bouthillier et al, 1998).…”
Section: Allergens Sensitization and Challengementioning
confidence: 99%